2012
DOI: 10.1088/0067-0049/199/2/32
|View full text |Cite
|
Sign up to set email alerts
|

X-RAY PHASE-RESOLVED SPECTROSCOPY OF PSRs B0531+21, B1509–58, AND B0540–69 WITH RXTE

Abstract: The Rossi X-ray Timing Explorer (RXTE) has made hundreds of observations on three famous young pulsars (PSRs) B0531+21 (Crab), B1509-58, and B0540-69. Using the archive RXTE data, we have studied the phase-resolved spectral properties of these pulsars in details. The variation of the X-ray spectrum with phase of PSR B0531+21 is confirmed here much more precisely and more details are revealed than the previous studies: the spectrum softens from the beginning of the first pulse, turns to harden right at the puls… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 46 publications
(91 reference statements)
19
51
0
Order By: Relevance
“…The radio pulse profile shows a sharp peak, while the X-ray profile has a single, broad, and asymmetric peak and lags the radio peak by about one quarter of the cycle (Kawai et al 1991). The broad X-ray pulse profile was conventionally described by two Gaussian components (Cusumano et al 2001;Ge -Chandra X-ray image of B1509 and its PWN in MSH 15-52 in the 0.5-7 keV band. All the X-ray events are projected onto the red dashed line in the CC mode observation to form a 1D image.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The radio pulse profile shows a sharp peak, while the X-ray profile has a single, broad, and asymmetric peak and lags the radio peak by about one quarter of the cycle (Kawai et al 1991). The broad X-ray pulse profile was conventionally described by two Gaussian components (Cusumano et al 2001;Ge -Chandra X-ray image of B1509 and its PWN in MSH 15-52 in the 0.5-7 keV band. All the X-ray events are projected onto the red dashed line in the CC mode observation to form a 1D image.…”
mentioning
confidence: 99%
“…A pulse phase-resolved spectral analysis showed that Γ remains stable during the pulsed phase, such that the spectra of the two components of the pulse shape are indistinguishable (Rots et al 1998). Ge et al (2012) presented a more comprehensive phase-resolved spectral analysis using 15 years of RXTE data with a total exposure time of ∼578 ks. They treated the 0.2 cycles off-pulse emission as the background and found that Γ increases from 1.33 to 1.47 as the flux decreases.…”
mentioning
confidence: 99%
“…As described in Ge et al (2012), the two asymmetrical pulses of the Crab pulsar in the X-ray band could be modeled by the formula (1) proposed by Nelson et al (1970). In this paper, we only fitted the shape of P1 of the X-ray profile to obtain its peak phase.…”
Section: Phase Calculation For Rxtementioning
confidence: 99%
“…( 2004)) or (6.6 ± 1.3) × 10 −7 period per day (MJD 51955-55142, Ge et al (2012)). Here we analyze more observations, in a longer time range MJD 51955-55927, and both PCA and HEXTE showed the same trend with the change rates of (5.0 ± 0.9) × 10 −7 and (4.5 ± 0.9) × 10 −7 period per day, respectively.…”
Section: The X-ray Phases From Pca and Hexte And Their Correlationmentioning
confidence: 99%
See 1 more Smart Citation